Medical Informatics and Education: The Profession as Gate-Keeper - Kluge, E.-H. W. (Methods of Information in Medicine, 1989)
Modern health care systems, both at the policy as well as the delivery level, are becoming increasingly data-dependent. The profession of Medical Informatics is beginning to emerge as a distinctive discipline that functions as the point of entry of the relevant data into the systems and as the medium of their manipulation. Medical Informatics therefore finds itself in a gate-keeper position: i. e., in the position of someone who effectively controls the use of these data and whose actions set the parameters of what will be done with them. This position, in turn, places special ethical obligations on the profession as a whole as well as on the individual professionals. It is unlikely that the nature of these obligations, or indeed their very scope, will be appreciated without some training in ethics; and it is also unlikely that the ethical problems that arise in the conduct of the profession can be handled smoothly without some ethical education. Medical Informatics, as a profession, should therefore insist that the education of its members involve not only technical parameters but also include some education in ethics. The pay-off for this would come not only in terms of an integrated functioning of the profession as a whole, but also in a much more firmly established legal and social position.
Keywords: Professional Ethics; Computing Milieu; Legal Issues; Patient Data Privacy; Curriculum